1987
DOI: 10.1111/j.1744-7348.1987.tb01467.x
|View full text |Cite
|
Sign up to set email alerts
|

The invertebrate population and response to pesticide treatment of two permanent and two temporary pastures

Abstract: S U M M A R YDuring 1979 and 1980 the herbage yields of two permanent pastures and two temporary swards were compared. All four swards received 250 kg N/ha per yr. The invertebrate population of all four swards was studied. Pot-worms (Enchytraeidae) and some species with long life cycles, e.g. wireworms (Agriotes spp.) were more numerous in the permanent swards, but aerial species were more numerous in the temporary swards. A range of pesticide treatments was applied. At one temporary sward site, application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…F. As with class B, any direct e!ect via the soil solution in this group may only occur with species that are highly sensitive to these compounds, but e!ects may also occur via ingestion and the risk of long-term e!ects due to accumulation is apparent. Way and Scopes (1968) found a short-term increase in enchytraeid abundance 2 months after application of the organophosphorus Phorate, possibly an indirect e!ect related with a decrease in other groups, but Clements et al (1987) reported a negative e!ect of repeated application of Phorate on the enchytraeids of several English grasslands. A number of persistent organochlorine pesticides belong to this group, and have been studied repeatedly in "eld experiments regarding the e!ect on enchytraeids.…”
Section: Pesticidesmentioning
confidence: 94%
See 1 more Smart Citation
“…F. As with class B, any direct e!ect via the soil solution in this group may only occur with species that are highly sensitive to these compounds, but e!ects may also occur via ingestion and the risk of long-term e!ects due to accumulation is apparent. Way and Scopes (1968) found a short-term increase in enchytraeid abundance 2 months after application of the organophosphorus Phorate, possibly an indirect e!ect related with a decrease in other groups, but Clements et al (1987) reported a negative e!ect of repeated application of Phorate on the enchytraeids of several English grasslands. A number of persistent organochlorine pesticides belong to this group, and have been studied repeatedly in "eld experiments regarding the e!ect on enchytraeids.…”
Section: Pesticidesmentioning
confidence: 94%
“…This may be explained by the amount applied (1.6 kg ) ha\) and the short half-life of this pesticide: only if C. sphagnetorum is highly sensitive to this pesticide could any e!ects have been expected. The application of the organochlorine Aldrin in an English pasture (Clements et al, 1987) and in coniferous litter (Heungens, 1970) appeared not to have an e!ect on the enchytraeid community.…”
Section: Pesticidesmentioning
confidence: 96%
“…With the aid of a continuous stream of water, this method can be an improvement on the simple act of flotation and has been used successfully when the root-feeding community is sought (e.g. Clements et al 1987). Sieving can also be combined with subsequent flotation in magnesium sulfate (Murray & Clements 1995) to separate small larvae from the debris remaining on the sieve.…”
Section: Flotation Methodsmentioning
confidence: 99%
“…Although some studies assessed enchytraeid community structures in grasslands, meadows and pastures, studying the influence of grazing (Schlaghamerský et al 2007), liming (Davidson et al 2004), fertilization (Sokołowska & Seniczak 2005) or pesticides (Clements et al 1987, Forsters et al 1992, Martin 1975, most of them only reported a total abundance of enchytraeids (e.g. Clements et al 1987, Francini et al 2014, Van Vliet et al 2006, without any details on species diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Clements et al 1987, Francini et al 2014, Van Vliet et al 2006, without any details on species diversity. Yet, several authors recommended identifying the individuals at least at the genus level and if possible at the species level (Pelosi & Römbke 2016).…”
Section: Introductionmentioning
confidence: 99%